2018
DOI: 10.1002/adma.201802912
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged CoO Covalency in Octahedral Sites Leading to Highly Efficient Spinel Oxides for Oxygen Evolution Reaction

Abstract: Cobalt-containing spinel oxides are promising electrocatalysts for the oxygen evolution reaction (OER) owing to their remarkable activity and durability. However, the activity still needs further improvement and related fundamentals remain untouched. The fact that spinel oxides tend to form cation deficiencies can differentiate their electrocatalysis from other oxide materials, for example, the most studied oxygen-deficient perovskites. Here, a systematic study of spinel ZnFe Co O oxides (x = 0-2.0) toward the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
297
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 375 publications
(318 citation statements)
references
References 42 publications
6
297
0
Order By: Relevance
“…Their catalytic activity depends on the electronic structure.I naspinel oxide lattice,e acho xygen anion is shared amongst its four nearest transition metal cations,ofwhich one is located within the tetrahedral interstices and the remaining three cations are in the octahedral interstices. [3,4] However,t he redox of late transition metal oxides (e.g., Coand Ni-based) could involve both the transition metal and oxygen ligand due to the increased orbital hybridization between TM 3d and O2 p. [2,5] Earlier reports had demonstrated that the energy in TM 3d orbital cannot be treated in isolation from O2pwhen there is significant overlap between TM 3d and O2 p. Recent studies on oxygen-deficient perovskite oxides reveal that the oxygen anion could also act as the redox partner in OER. The charge of oxygen anion tends to shift toward the octahedral-occupied Co instead of tetrahedraloccupied Co,w hich hence produces strong orbital interaction between octahedral Co and O. Thus,t he OER activity can be promoted by pushing more Co into the octahedral site or shifting the oxygen charge towards the redox-active metal center in CoO 6 octahedra.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Their catalytic activity depends on the electronic structure.I naspinel oxide lattice,e acho xygen anion is shared amongst its four nearest transition metal cations,ofwhich one is located within the tetrahedral interstices and the remaining three cations are in the octahedral interstices. [3,4] However,t he redox of late transition metal oxides (e.g., Coand Ni-based) could involve both the transition metal and oxygen ligand due to the increased orbital hybridization between TM 3d and O2 p. [2,5] Earlier reports had demonstrated that the energy in TM 3d orbital cannot be treated in isolation from O2pwhen there is significant overlap between TM 3d and O2 p. Recent studies on oxygen-deficient perovskite oxides reveal that the oxygen anion could also act as the redox partner in OER. The charge of oxygen anion tends to shift toward the octahedral-occupied Co instead of tetrahedraloccupied Co,w hich hence produces strong orbital interaction between octahedral Co and O. Thus,t he OER activity can be promoted by pushing more Co into the octahedral site or shifting the oxygen charge towards the redox-active metal center in CoO 6 octahedra.…”
mentioning
confidence: 99%
“…[1b, 2] Better understanding of the OER reaction on TM oxides is necessary to this end. Spinel oxides, ah uge crystal family for oxygen electrocatalysis, [2,4,8] require more complex analysis because the tetrahedral and octahedral interstice can accommodate the same TM. [3] Thec onventional perception of oxygen evolution regards the redox-active metallic center as the active site and it is the redox ability of TM that mediates the transition of [M n+ ÀOH ad ]/[M n+1 ÀO ad ]d uring OER.…”
mentioning
confidence: 99%
See 3 more Smart Citations